Enhancing the self-esteem of undergraduates in a Malaysian higher education institution through bibliotherapy - Lourdunathan, Josephine; Idris, Khairuddin; Mokhtar, Halimatun Halaliah; Vethamani, Malachi Edwin (Universiti Putra Malaysia Press, 2012)
The purpose of this study was to explore the use of bibliotherapy or therapeutic experience of reading young adult literature among a group of young adults in developing their self-esteem. Participants consisted of six undergraduate students pursuing a degree in a Malaysian higher education institution. The phenomenological method was employed to explore the participants’ reading of young adult literature. These participants read young adult literature, and shared their thoughts, feelings and experiences on the reading phenomenon through dialogue journals. Data triangulation was carried out by analyzing and comparing findings from observations made by two informants, researcher’s field notes, in-depth pre-and-post interviews. The study discovered that the undergraduates are aware of the importance of self-esteem and how their personal struggles have affected their level of self-esteem. Some of their challenges include identity crisis, lack of self-confidence and poor family relationship. The reading process has contributed to the success of developing self-esteem among the participants. Reading young adult literature has helped the participants to experience a new level of self-confidence, gain new understanding of self, feel less different, and inspired them to grow positively. Five reading characteristics contributing to the effectiveness of reading young adult literature for self-esteem emerged. The five types of reading characteristics include intentional, relational, reflective, transporting and pleasure. The findings of this study suggest that literature can be a catalyst for personal development for young adults in the Malaysian educational institutions.